Localized high grade endometrial stromal sarcoma and localized undifferentiated uterine sarcoma: a retrospective series of the French Sarcoma Group. Issue 4 (16th February 2019) - Meurer, Marie; Floquet, A; Ray-Coquard, I; Bertucci, F; Auriche, M; Cordoba, A; Piperno-Neumann, S; Salas, S; Delannes, M; Chevalier, T; Italiano, A; Blay, J Y; et al.
Abstract : Objective: High grade endometrial stromal sarcoma and undifferentiated uterine sarcomas are associated with a very poor prognosis. Although large surgical resection is the standard of care, the optimal adjuvant strategy remains unclear. Methods: A retrospective analysis of patients with localized high grade endometrial stromal sarcoma and undifferentiated uterine sarcomas (stages I–III) treated in 10 French Sarcoma Group centers was conducted. Results: 39 patients with localized high grade endometrial stromal sarcoma and undifferentiated uterine sarcomas treated from 2008 to 2016 were included. 24/39 patients (61.5%) were stage I at diagnosis. 38/39 patients underwent surgical resection, with total hysterectomy and bilateral oophorectomy completed in 26/38 (68%). Surgeries were mostly resection complete (R0, 23/38, 60%) and microscopically incomplete resection (R1, 6/38, 16%). 22 patients (58%) underwent postoperative radiotherapy (including brachytherapy in 11 cases), and 11 (29%) underwent adjuvant chemotherapy. After a median follow-up of 33 months (range 2.6–112), 17/39 patients were alive and 21/39 (54%) had relapsed (9 local relapses and 16 metastases). The 3 year and 5 year overall survival rates were 49.8% and 31.1%, respectively, and 3 year and 5 year disease free survival rates were 42.7% and 16.0%, respectively. Median overall survival and disease free survival were 32.7 (95% CI 16.3–49.1) and 23 (4.4–41.6) months, respectively. Medians were, respectively, 46.7 months and 39.0 months among those who underwent adjuvant radiotherapy and 41.0 months and 10.3 months for those who underwent adjuvant chemotherapy. In multivariate analysis, adjuvant radiotherapy was an independent prognostic factor for overall survival (P=0.012) and disease free survival (P=0.036). Chemotherapy, International Federation of Gynecology and Obstetrics I–II stages, and Eastern Cooperative Oncology Group-performance status 0 correlated with improved overall survival (P=0.034, P=0.002, P=0.006), and absence of vascular invasion (P=0.014) was associated with better disease free survival. Conclusions: The standard treatment of primary localized high grade endometrial stromal sarcoma and undifferentiated uterine sarcomas is total hysterectomy and bilateral oophorectomy. The current study shows that adjuvant radiotherapy and adjuvant chemotherapy appear to improve overall survival. A prospective large study is warranted to validate this therapeutic management.